New‐onset ulcerative colitis in pregnancy associated to toxic megacolon and sudden fetal decompensation: Case report and literature review. Issue 7 (7th May 2019) - Brunelli, Roberto; Perrone, Seila; Perrone, Giuseppina; Galoppi, Paola; De Stefano, Maria G.; Maragno, Anna M.; Cesarini, Monica; De Carolis, Aurora; Masselli, Gabriele; Vernia, Piero
Abstract: Ulcerative colitis (UC) is a chronic inflammatory disease rarely arising during gestation. Because the available information is based on case reports or small retrospective studies, diagnosis may be difficult and treatment is still controversial. A case of toxic megacolon developing in late pregnancy associated to a sudden fetal decompensation is described. Diagnostic and clinical topics of acute UC onset in pregnancy are debated.A primipara, 34 years old, 33/0 weeks of gestation, was admitted with a diagnosis of preterm labor, associated to acute bloody diarrhea (up to 10 daily motions) and cramping abdominal pain. A diagnosis of new‐onset early‐stage UC was made by sigmoidoscopy. An intensive care regimen including hydrocortisone, antibiotics and parenteral nutrition was immediately started. Magnetic resonance imaging of maternal abdomen, fostered by the worsening patient conditions, evidenced dilatation of the entire colon and a severely hampered of fetal muscular tone.Toxic megacolon complicated by superimposed Clostridium difficile infection was associated to a sudden fetal decompensation diagnosed by chance during maternal abdominal magnetic resonance imaging. An emergency cesarean section was mandatory. According to a senior surgeon's decision, total colectomy was not immediately performed following cesarean section with reference to the absence of colonic perforation. We obtained a good short‐term maternal outcome and an uncomplicated neonatal course. Counseling of those patients must be focused on timely and multidisciplinary intervention in order to improve the course of maternal disease and to prevent fetal distress.